Maximising Olympic Distance performance - The athlete`s perspective - Hill, C. (Proceedings from the Gatorade International Triathlon Science II Conference, Noosa, Australia, November 7-8, 1999: Maximising Olympic Distance Triathlon Performance: A multi-disciplinary perspective, 1999)
Preparation is not just the physical training in the months leading up to the event. There are psychological, emotional, dietry, health and circumstantial components that are critical to performance. A balance must be kept between these. An obvious but important factor is the sporting career of the athlete. Most elite athletes have dedicated themselves to sport from a very young age. With this span of time comes wins and lossess and constant competitive experience. Understanding how an elite triathlete maximises Olyimpic Distance Triathlon Performance is as complicated as it is personal. This paper will discuss these themes in the context of Chris Hills carriere as an elite triahtlete since 1991.